A COMPARATIVE STUDY OF PSYCHOLOGICAL BURNOUT LEVELS AMONG TEACHERS OF PHYSICAL EDUCATION AND SPORTS IN MIDDLE AND SECONDARY STAGES (ALGERIA-EL BAYADH) - Larbi Mohammed,; Guezgouz Mohamed,; Mokrani Djamel, (Sport Scientific And Practical Aspects, 2025)
The objective of the study is to determine the degree of extent of the phenomenon of psychological exhaustion among teachers of physical education and sports at the secondary and middle levels of education. For this study, the researchers relied on the descriptive approach for it fits the subject of the study. The sample consisted of (60) teachers, including (40) of the average level of education chosen at random. The researchers opted for the burnout scale introduced by Seidman and Zager 1994 and translated into Arabic by Adel Abdullah (1994). After statistical treatment, the results showed that teachers of physical education and sports are characterized by moderate degrees of psychological exhaustion. The study also revealed statistically significant differences in favor of middle school teachers.